2015
DOI: 10.3945/jn.114.206359
|View full text |Cite
|
Sign up to set email alerts
|

Usual Dietary Energy Density Distribution Is Positively Associated with Excess Body Weight in Mexican Children ,

Abstract: A positive association between usual DED and OW/O was found in Mexican children. The association was stronger when only plausible reporters were considered. This suggests that there is a need for strategies to reduce energy density in the diet of Mexican children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 28 publications
2
15
0
1
Order By: Relevance
“…Kral et al suggested that sample size (n 49) might have been too small to detect significant association between the two variables. Moreover, although 3-d weighed food records were used in the previous study, there was no control for under-reporters that have shown to affect the results in our and previous studies (15,23,53) .…”
Section: Discussionmentioning
confidence: 94%
“…Kral et al suggested that sample size (n 49) might have been too small to detect significant association between the two variables. Moreover, although 3-d weighed food records were used in the previous study, there was no control for under-reporters that have shown to affect the results in our and previous studies (15,23,53) .…”
Section: Discussionmentioning
confidence: 94%
“…In children, evidence of the association of DED with OW/O is weaker [ 11 , 20 , 21 ] and is related with the ability [ 22 , 23 ] or inability [ 24 , 25 ] to compensate for energy intake. However, some observational studies have documented that high DED intake leads to increased adiposity [ 20 , 26 ] and weight gain [ 27 ]. In adolescents, the evidence is inconsistent [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The evidence linking dietary intakes and PA with obesity among children and adolescents is inconclusive and contradictory. [ 8 9 10 ] Energy intakes in children and adolescents have shown a small or no association with weight status in previous epidemiologic studies, partly because of a possibly underreported dietary intake. [ 11 12 ] Several studies on overweight and obesity among children and adolescents indicate a significant association between weight status and PA.[ 13 ] To date, most studies focused on either PA or dietary intakes, and few took both into account.…”
Section: Introductionmentioning
confidence: 99%